Bile Acid‐Induced Toxicity in HepaRG Cells Recapitulates the Response in Primary Human Hepatocytes. Issue 2 (13th August 2015) - Woolbright, Benjamin L.; McGill, Mitchell R.; Yan, Huimin; Jaeschke, Hartmut
Abstract: Cholestatic liver injury is a pathological component of numerous disease states. Much of the current literature on cholestatic liver injury is derived from in vitro studies using rodent hepatocytes or cell lines transfected with bile acid (BA) uptake transporters. While these studies demonstrate BA‐driven apoptosis, it is debatable whether these models reflect the human pathophysiology, as primary human hepatocytes undergo primarily necrosis. HepaRG cells are a bipotential, human hepatoma line that express apical and basolateral BA transporters. Thus, we sought to determine whether HepaRG cells could replicate the response of primary human hepatocytes to BA exposure in vitro . HepG2 cells, primary murine hepatocytes (PMH) or HepaRG cells, were exposed to taurocholic acid (TCA), or glycochenodeoxycholate (GCDC) and lactate dehydrogenase release were measured to determine cell death. Cell death occurred dose‐responsively in HepaRG cells when exposed to GCDC; however, HepG2 cells died acutely only at very high concentrations of GCDC. In HepaRG cells, pre‐treatment with the caspase inhibitor z‐VD‐FMK had no effect on cell death, indicating a lack of apoptotic cell death, and while c‐jun N‐terminal kinase (JNK) protein was activated by GCDC treatment in HepaRG cells, the inhibition of JNK did not protect. Although previous data indicate that TCA stimulates pro‐inflammatory gene induction in PMH, there was no change in gene expression after TCA stimulation in HepaRG cells, which mimicked previous data found in primary human hepatocytes. These data provide evidence for HepaRG cells as a new model for the study of the effect of BA on human hepatocytes.